Comparison of the processing conditions and the properties of granules made from fly ash of lignite and coal. (1st March 2020) - Borowski, Gabriel; Ozga, Małgorzata
Graphical abstract: Highlights: The properties of granules from fly ash of coal and lignite were compared. The required humidity was assigned depending of type of fly ash. Granulation index for favorable processing of ashes was developed. The mass fraction share of fly ash was agreed for the grains lesser than 0.063 mm. Granulation of coal fly ash was more effective and preferable granules produced. Abstract: The article presents the results pertaining to granulation of two types of fly ash from (1) coal (hard coal) incineration and (2) lignite (brown coal) combustion. The physical, chemical and mechanical properties of granules were compared to obtain the good quality of aggregates. Three types of binders were added to the ash blends: hydrated lime, Portland cement and phosphogypsum. The experimental technological line was used for pelletizing the fine mixtures; then, the obtained granules were tested immediately after their manufacturing (in fresh state) as well as after curing. The addition of binder improved their mechanical properties. Granulation of powders regimented with strictly defined shares of grains fraction. The axial compression test was conducted to find the best toughness, with consideration of the curing time of granules. Granules in the diameter of 15–18 mm were obtained using a disc granulator. The comparison revealed that the granulation of coal fly ash was more effective because of the processing conditions, and the obtained bodies were characterized by better mechanical properties then those made of the lignite fly ash.